2001
DOI: 10.2307/1543522
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Dissection of Gravity-Dependent Mechanical Orientation in Gravitactic Microorganisms

Abstract: Mechanisms of gravitactic behaviors of aquatic microorganisms were investigated in terms of their mechanical basis of gravity-dependent orientation. Two mechanical mechanisms have been considered as possible sources of the orientation torque generated on the inert body. One results from the differential density within an organism (the gravity-buoyancy model) and the other from the geometrical asymmetry of an organism (the drag-gravity model). We first introduced a simple theory that distinguishes between these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 14 publications
3
49
0
Order By: Relevance
“…Despite the absence of a statocyst-like structure, our results support early observations that larval urchins have mechanoreception ability and are capable of adjusting their propulsive behaviors accordingly [59,84,85]. Further work on ciliary motion control [86,87] and gene expression (e.g., orthologs of vertebrate mechanosensory genes, e.g.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Despite the absence of a statocyst-like structure, our results support early observations that larval urchins have mechanoreception ability and are capable of adjusting their propulsive behaviors accordingly [59,84,85]. Further work on ciliary motion control [86,87] and gene expression (e.g., orthologs of vertebrate mechanosensory genes, e.g.…”
Section: Discussionsupporting
confidence: 87%
“…Ontogenetic changes in larval shape may play a role in the larval ability to maintain an upright orientation, and hence, stability in flow. Older, heavier larval urchins have increased skeleton weight as ballast which could enhance stability [78,59]. However, the additions of arms and increased size could also compromise stability by affecting the separation distance between the center of gravity and center of buoyancy [78].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…P av would increase when there is an increase in the fraction of cells orienting upwards. Mogami et al (2001) demonstrated that the gravitactic orientation of Paramecium is mechanically biased by the torque generated mainly due to the fore-aft asymmetry of the cell body. The upward-orienting torque increases in proportion to gravity, so that the fraction of cells orienting upwards, i.e., F(φ) for a large φ, increases under hypergravity, and decreases under microgravity.…”
Section: Discussionmentioning
confidence: 99%